Impact of age on the survival of patients with liver cancer: an analysis of 27,255 patients in the SEER database - Zhang, Wenjie (Oncotarget, 2015)
BACKGROUND & AIMS: The risk of liver cancer (LC) is regarded as age dependent. However, the influence of age on its prognosis is controversial. The aim of our study was to compare the long-term survival of younger versus older patients with LC. METHODS: In this retrospective study, we searched Surveillance, Epidemiology, and End-Results (SEER) population-based data and identified 27,255 patients diagnosed with LC between 1988 and 2003. These patients were categorized into younger (45 years and under) and older age (over 45 years of age) groups. Five-year cancer specific survival data was obtained. Kaplan–Meier methods and multivariable Cox regression models were used to analyze long-term survival outcomes and risk factors. RESULTS: There were significant differences between groups with regards to pathologic grading, histologic type, stage, and tumor size (p < 0.001). The 5-year liver cancer specific survival (LCSS) rates in the younger and older age groups were 14.5% and 8.4%, respectively (p < 0.001 by univariate and multivariate analysis). A stratified analysis of age on cancer survival showed only localized and regional stages to be validated as independent predictors, but not for advanced stages. CONCLUSIONS: Compared to older patients, younger patients with LC have a higher LCSS after surgery, despite the poorer biological behavior of this carcinoma.